2012
DOI: 10.1002/jbm.b.32771
|View full text |Cite
|
Sign up to set email alerts
|

In vitro response of osteoarthritic chondrocytes and fibroblast‐like synoviocytes to a 500–730 kDa hyaluronan amide derivative

Abstract: The aim of this study was to compare the effects of native hyaluronan (HA) with that of its hexadecylamide derivative (HYADD) on proliferation of fibroblast-like synoviocytes (FLS) and chondrocytes. The production of inflammatory and anti-inflammatory cytokines was also analyzed in FLS cultures. The proliferation of osteoarthritis (OA) chondrocytes was enhanced when cells were treated with 0.5-1.5 mg mL(-1) of HA or HYADD®4-G. This effect was completely suppressed by the anti-CD44 antibody. At 0.5 to 1 mg mL(-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 47 publications
2
33
0
1
Order By: Relevance
“…rhPRG4 prevents IκBα degradation in a CD44-dependent manner; this is consistent with its ability to inhibit IL-1-induced NFκB nuclear translocation. This observation extends the efficacy of rhPRG4 as a biologic agent that inhibits synoviocyte proliferation in RA and OA, and establishes a role for CD44 in modulating OA synoviocyte proliferation [38]. The role of PRG4 in modulating OA synoviocyte proliferation is further highlighted by the ability of PRG4 in SF to reduce OA synoviocyte proliferation.…”
Section: Discussionsupporting
confidence: 57%
“…rhPRG4 prevents IκBα degradation in a CD44-dependent manner; this is consistent with its ability to inhibit IL-1-induced NFκB nuclear translocation. This observation extends the efficacy of rhPRG4 as a biologic agent that inhibits synoviocyte proliferation in RA and OA, and establishes a role for CD44 in modulating OA synoviocyte proliferation [38]. The role of PRG4 in modulating OA synoviocyte proliferation is further highlighted by the ability of PRG4 in SF to reduce OA synoviocyte proliferation.…”
Section: Discussionsupporting
confidence: 57%
“…Cells remained viable throughout all experiments, with preliminary trials revealing no change in cell numbers with any treatment (data not shown) as previously published [22]. Some HSF detached from the culture well surface in the absence of FBS and this phenomenon was exacerbated in the presence of HA.…”
Section: Resultssupporting
confidence: 79%
“…The interaction of unmodified HA with CD44 is important in suppression of IL-1β-stimulated effects in cultured chondrocytes [15,38,42,53] and synovial fibroblasts [49]. CD44 is also involved in the stimulation of OA chondrocyte proliferation by the amide derivative of HA [22]. We were able to demonstrate amelioration of a few of the effects of the derivatized HA on gene expression using a CD44 blocking antibody in confluent cultures of HAC and HSF supporting a role for this cell-surface receptor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Smith et al demonstrated that this HA derivative reduced the expression in OA of key proteolytic enzymes implicated in cartilage degradation such as matrix metalloproteinase (MMP)1, MMP13, disintegrin and metalloproteinases with thrombospondin motifs (ADAMTS)4, ADAMTS5, as well as the production of inflammatory mediators such as IL‐6 . An upregulation of anti‐inflammatory cytokine expression such as IL‐10 has also been shown …”
Section: Introductionmentioning
confidence: 99%